Assessment of Imaging Features of Crohn’s Disease with MR Enterography - Onay, Mehmet; Erden, Ayşe; Binboğa, Ali Burak; Altay, Çetin Murat; Törüner, Murat (Turkish Journal of Gastroenterology, 2021)
Background: To evaluate the frequency of pathological findings determined on magnetic resonance (MR) enterography (MRE) inpatients with Crohn’s Disease.Methods: A retrospective analysis of the MRE images was made in 34 female and 41 male patients (mean age 41 years) with Crohn’s disease.The prevalence of bowel wall (mural thickening, mural edema, mural fat deposits, mucosal enhancement, ulceration, cobblestoneappearance, pseudopolyps) and mesenteric fatty tissue alterations (fatty tissue proliferation, mesenteric hypervascularity, enlargedlymph nodes, peri-enteric inflammation, reactive fluid), complications due to penetrating (fistula, sinus tract, abscess) and stenosingprocesses (fibrotic and inflammatory stenosis, obstruction, dilatation), and involvement of the colon were determined.Results: The most frequently observed changes in the bowel wall and mesenteric fatty tissue were mural thickening (98.7%) andenlargement of mesenteric lymph nodes (76%), respectively. Stenosis was the most common complication (76%). The most frequentlyseen pathology of the colon was ileocecal valve thickening and enhancement (74.7%).Conclusion: MR enterography is a useful imaging modality for the evaluation of changes in both the mesenteric fatty tissue and thebowel wall. As there is no use of ionizing radiation, MR enterography should be the preferred imaging modality during follow-up ofpatients with Crohn’s disease.